2014
DOI: 10.1111/jphp.12294
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir, a novel nucleotide analogue inhibitor used for the treatment of hepatitis C virus

Abstract: Objective To provide an overview of a novel anti-hepatitis C agent, sofosbuvir. Key findings Sofosbuvir is a novel nucleotide analogue inhibitor of hepatitis C virus (HCV) NS5B polymerase that has recently been approved by the Federal Drug Administration for the treatment of HCV genotypes 1, 2, 3 or 4 in a variety of patients. The emergence of such a novel treatment provides benefit to previously untreated genotypes and patient populations, with little chance of promoting significant viral resistance. Excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 35 publications
0
24
0
1
Order By: Relevance
“…The latter group includes compounds that target viral polymerase functions and represent a promising avenue for antiviral exploration. Such compounds are already used to treat other viral infections, including those by human immunodeficiency virus type 1 (HIV-1) (12,13) and hepatitis B and C viruses (14,15). Influenza A viruses have three polymerase proteins: basic polymerase 1 (PB1) is an RNA-dependent RNA polymerase (RdRp); basic polymerase 2 (PB2) binds host-cell capped mRNAs; and the acid polymerase (PA) possesses endonuclease activity that results in removal of the mRNA caps (16).…”
mentioning
confidence: 99%
“…The latter group includes compounds that target viral polymerase functions and represent a promising avenue for antiviral exploration. Such compounds are already used to treat other viral infections, including those by human immunodeficiency virus type 1 (HIV-1) (12,13) and hepatitis B and C viruses (14,15). Influenza A viruses have three polymerase proteins: basic polymerase 1 (PB1) is an RNA-dependent RNA polymerase (RdRp); basic polymerase 2 (PB2) binds host-cell capped mRNAs; and the acid polymerase (PA) possesses endonuclease activity that results in removal of the mRNA caps (16).…”
mentioning
confidence: 99%
“…In a small cohort of GT 5 and 6 patients, the SVR12 was reported as 100%. Subsequent studies demonstrated that even in difficult-to-treat patient populations such as AfricanAmericans, HIV coinfected and liver transplant patients, sofosbuvir regimens demonstrated high cure rates [17,52,56].…”
Section: Sofosbuvir Clinical Studiesmentioning
confidence: 99%
“…These combination regimens have produced cure rates between 95% and 99% with only 8-12 weeks of therapy. Sofosbuvir has been proven effective in many patient populations that include cirrhotics, patients with advanced liver disease, liver transplant patients and patients who have not responded to other therapies [17].…”
Section: Introductionmentioning
confidence: 99%
“…3,5-Di-O-benzoyl-2-deoxy-2-fluoro-2-C-methyl-D-ribono-clactone 1 is an important intermediate for the preparation of sofosbuvir 2, a highly effective drug recently approved for treating chronic hepatitis C. 1 Some other nucleoside HCV NS5B polymerase inhibitors currently under preclinical or clinical studies are also synthesized through this intermediate. [2][3][4][5][6] By now, there have been several routes reported for preparing 1 (Fig.…”
Section: Introductionmentioning
confidence: 99%